2018
DOI: 10.18203/2320-6012.ijrms20182299
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-radiological variability of pulmonary tuberculosis in young patients as compared to elder patients prior to RNTCP and after 18 years RNTCP

Abstract: Background: Tuberculosis, a chronic disease causing high morbidity and mortality with multiple host related and socio-demographic risk factors. Incidence is 3-4 times among in diabetics. HIV is considered to be a most powerful risk factor other being malnutrition, Tubercular contacts, smoking habits and alcoholism. Many ecological and societal threats increase a vulnerability to infection and succession of the disease. Objective was to study and compare various clinico-radiological presentations and clinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
3
2
0
Order By: Relevance
“…The proportion of elderly TB observed in our study (14.9%) is similar to that observed in previous studies conducted in India such as Karnataka (18.7%) [33], Tamil Nadu (14%) [34] and Punjab (12.3%) [35] and other countries such as Nigeria [36], Uganda [8], Taiwan [9] and United States [10]. However, this might be expected to increase over time given the increasing life expectancy in India.…”
Section: Plos Onesupporting
confidence: 87%
See 2 more Smart Citations
“…The proportion of elderly TB observed in our study (14.9%) is similar to that observed in previous studies conducted in India such as Karnataka (18.7%) [33], Tamil Nadu (14%) [34] and Punjab (12.3%) [35] and other countries such as Nigeria [36], Uganda [8], Taiwan [9] and United States [10]. However, this might be expected to increase over time given the increasing life expectancy in India.…”
Section: Plos Onesupporting
confidence: 87%
“…This finding is in line with the epidemiological trend of TB in India (males are more affected than females) [37,38]. Previous studies conducted in India and other LMIC countries have also reported that elderly males have higher rate of TB than females [33][34][35][36]. Possible reasons for this pattern could be better healthcare service accessibility and higher rate of social interaction among males [39,40].…”
Section: Plos Onesupporting
confidence: 85%
See 1 more Smart Citation
“…As per a study by Lee et al, there was a significant association of hemoptysis and breathlessness in the younger and elderly age groups, respectively [11]. Studies from Patiala, India as well as from Egypt demonstrated a significant association of fever, hemoptysis, and weight loss in younger patient, and dyspnea and chest pain in the older age group [12,13]. Potential explanations for this disparity may be the variation in patient characteristics, smaller sample size, and single-center data.…”
Section: Discussionmentioning
confidence: 78%
“…28 Despite having better compliance with drug therapy, the elderly patients showed a lower sputum conversion rate at the end of 2 months of treatment when compared to younger patients. [29][30][31] The results of some studies suggest that the high incidence of adverse drug reactions, drug interactions, and complications may lead to dose reduction and malabsorption of anti-TB drugs. 32 Other studies attribute the low sputum negative conversion rate at the end of the intensive phase to the delayed sputum conversion and excretion caused by high bacterial loads.…”
Section: Discussionmentioning
confidence: 99%